Stereotactic Radiosurgery for Cystic Vestibular Schwannomas. Issue 1 (4th August 2016) - Frisch, Christopher D.; Jacob, Jeffrey T.; Carlson, Matthew L.; Foote, Robert L.; Driscoll, Colin L.W.; Neff, Brian A.; Pollock, Bruce E.; Link, Michael J.
Abstract: BACKGROUND: The optimum treatment for cystic vestibular schwannoma (VS) remains controversial. Anecdotally, many treating physicians feel that cystic VSs do not respond to stereotactic radiosurgery (SRS) as well as noncystic tumors. OBJECTIVE: To present outcomes after treatment of predominantly cystic VS with SRS. METHODS: A prospectively maintained clinical database of patients undergoing Gamma Knife (Elekta Instruments, Stockholm, Sweden) radiosurgery (GKRS) for VS at a single tertiary academic referral center was retrospectively reviewed. Patients diagnosed with cystic VS who were treated with GKRS between 1997 and 2014 were analyzed. Size-matched solid tumors treated with GKRS during this period were selected as controls. RESULTS: Twenty patients (12 women; median age at treatment, 56 years; range, 36-85 years) with cystic VS met inclusion criteria. The median radiologic follow-up within the cystic group was 63 months (range, 17-201 months), and the median change in tumor size was −4.9 mm (range, −10.4 to 9.3 mm). Sixteen tumors (80%) shrank, 2 (10%) remained stable, and 2 (10%) enlarged, accounting for a tumor control rate of 90%. The median radiologic follow-up in the noncystic control group was 67 months (range, 6-141 months), and the median change in size was −2.0 mm (range, −10.4 to 2.5 mm). Tumor control in the solid group was 90%. Comparing only those tumors that decreased in size showed that there was a trend toward a greater reduction within the cystic group ( P = .05). CONCLUSION: The present study demonstrates that tumor control after SRS for cystic VS may not differ from that of noncystic VS in selected cases.